Reducing air pollution with hybrid-powered robotic tractors for precision agriculture. (March 2016) - Gonzalez-de-Soto, Mariano; Emmi, Luis; Benavides, Carmen; Garcia, Isaias; Gonzalez-de-Santos, Pablo
Abstract : A hybrid energy system used in robotic tractors for precision weed and pest control in agriculture is evaluated and its exhaust emissions compared with the use of an internal combustion engine as a single power source. The agricultural implements require power for hydraulic pumps and fans which, initially, was provided by a power take-off system (PTO), wasting a lot of energy. The objectives of this work were to design and assess a hybrid energy system including the removal of the alternators from the tractor and the modification of the agricultural implements to replace the PTO power with electric power, using small pumps and small fans. These changes improved energy use and reduced the atmospheric pollution emission from the internal combustion engine. The hybrid energy system used the original combustion engine of the tractor in combination with a new electrical energy system, which consisted of a hydrogen fuel cell. An analysis of the exhaust gases using the internal combustion engine as the single power source and using the hybrid energy system was carried out to compare the results obtained. The results showed a reduction in emissions of almost 50% for the best case. Highlights: Reduction of the atmospheric pollutant emissions without loss of autonomy. Analysis of the exhaust gases in precision agriculture using robotic tractors. Hybrid energy system in robotic tractors for weed and pest control. System based on H2 fuel cell, batteries, PV energy and internal combustion engine. Results obtained experimentally using real agricultural machines.